Numerical Simulation of Water Quenching of Large Size Steel Forgings: Effects of Macrosegregation and Grain Size on Phase Distribution - Mountadar Lyassami; Davood Shahriari; Emna Ben Fredj; Jean-Benoit Morin; Mohammad Jahazi (Journal of Manufacturing and Materials Processing, 2018)
In this paper, water quenching of large ingots was simulated using FORGE NxT 1.1® Finite Element code. Simulations were carried out for as-forged medium-carbon low-alloy steel. A novel method is proposed to simulate the different parts of a large size forged block with different chemical compositions and grain sizes using the multiple materials method. The effects of macrosegregation, grain size variation and cooling rate on phase distribution through the volume of the forged block were investigated. The delay in transformation kinetics, which is due to the effect of grain size variation and carbon content, was analyzed. Results show that macrosegregation and grain size variations significantly influence transformation start points and the volume fraction of phases that are present in each location of the forged ingot. The proposed prediction method was validated using high-resolution dilatometry experiments and X-ray diffraction measurements to evaluate accurately the volume fraction of martensite, bainite and the percentage of retained austenite for each condition.